Incidence and characteristics of time-loss injuries in competitive fencing: a prospective, 5-year study of national competitions - Harmer, P. A. (Clinical Journal of Sport Medicine, 2008)
Objective: To estimate the incidence of time-loss injuries in competitive fencing and to characterize these injuries regarding type and location.